2004
DOI: 10.1002/fuce.200400005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Methanol Crossover on the DMFC

Abstract: A mathematic model is established to simulate the effects of methanol crossover on the DMFC. The transport and reactions of both oxygen and methanol at the cathode are described and the theory of “parallel electrode reactions” is applied to calculate the cathode over‐potential caused by methanol crossover. The influence of methanol concentration, fuel cell temperature, oxygen pressure, and membrane properties on the cathode over‐potential is evaluated. Simulation results show that methanol crossover considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Consequently, a simultaneous and equivalent increment of proton conductivity and methanol permeability would not cause any change on the DMFC performance. However, many authors have empirically demonstrated that proton conductivity is the main parameter governing the DMFC performance during standard operating conditions [33][34][35]. This is explained by the fact that methanol is electrochemically oxidized at the anode and, thereby, the driving force for methanol permeation, that is the concentration gradient, diminishes with increasing current density.…”
Section: Proton Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a simultaneous and equivalent increment of proton conductivity and methanol permeability would not cause any change on the DMFC performance. However, many authors have empirically demonstrated that proton conductivity is the main parameter governing the DMFC performance during standard operating conditions [33][34][35]. This is explained by the fact that methanol is electrochemically oxidized at the anode and, thereby, the driving force for methanol permeation, that is the concentration gradient, diminishes with increasing current density.…”
Section: Proton Conductivitymentioning
confidence: 99%
“…This is in agreement with the empirical evidence that DMFC performance is mainly governed by proton conductivity of the membrane. This is a consequence of methanol crossover to decrease with increasing current density, thus becoming ohmic losses the dominant parameter [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…At higher current densities the results may differ as the electro-osmotic effect will become more significant while the gradient concentration will diminish due to the increased methanol consumption at the anode [23]. Generally, methanol transport across the membrane and methanol crossover over-potential at the cathode both decrease with increasing current density [23][24][25].…”
Section: Introductionmentioning
confidence: 96%
“…Generally, methanol transport across the membrane and methanol crossover over-potential at the cathode both decrease with increasing current density [23][24][25]. Thus, methanol permeability predominates at low current density (via over-potential losses at cathode) while proton conductivity predominates at high current density (via ohmic losses in membrane) on the DMFC performance [23]. In principle, neglecting mass transport phenomena in gas diffusion layers (GDLs), results obtained in situ at open circuit voltage (OCV) conditions, if CO 2 and unreacted methanol are analyzed, should be equivalent to those values measured by ex situ methods.…”
Section: Introductionmentioning
confidence: 98%
“…Direct methanol fuel cells (DMFCs) have attracted much interest, due to their advantages of compact size, high fuel efficiency, environment friendly, and high power density [1][2][3][4][5]. In a DMFC, methanol is oxidized at the anode to form protons, electrons, and carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%